Organizational Culture and its Impact on Organizational Loyalty in the Private on Alshamel Clinical Laboratory in Al. Madinah Al. Monawarah (The International Journal for Scientific Research, 2024)
This study aimed to know the organizational culture and its impact on organizational loyalty in the private health sector in Medina. The study was an attempt to know the relationship between organizational culture and organizational loyalty in the comprehensive laboratory for medical analysis, which represents a private health sector from the sectors of Medina, to study the impact of organizational culture, which is represented by (policies and procedures, organizational values, behavioral patterns) on organizational loyalty, which is represented by (emotional loyalty, moral loyalty). The questionnaire was used to measure the variables using the Likert scale method. The research community consisted of all employees under the comprehensive laboratory for medical analysis, including health staff, administrators and workers. The study was applied to the entire facility and its branches, which numbered 25 employees in the comprehensive laboratory for medical analysis, in March, April, May, during this year 2023. The study concluded that there is a statistically significant moral impact of organizational culture, which is represented by (policies and procedures, organizational values, behavioral patterns) on organizational loyalty, which is represented by (emotional loyalty, moral loyalty). The study recommended promoting an organizational culture based on values, focusing on values ​​as they play a role in achieving organizational commitment, investing in employee development and training in addition to the continuous evaluation and adaptation of organizational culture.
Keywords: Organizational Culture; Organizational Loyalty; Health Sector